Engine valve seat ring and its preparation process and application
By using Fe-based alloy matrix and TWIP steel powder in the valve seat and using magnetron sputtering and temperature pressing technology, the wear, corrosion and cutting difficulty of the valve seat in high temperature environments is solved, and higher hardness, wear resistance and service life are achieved.
Patent Information
- Application Number
- CN202411968994.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-01
AI Technical Summary
Existing valve seats are prone to wear, corrode and difficult to cut under high temperature, high pressure and high speed friction environments, resulting in short service life and difficult processing.
The Fe-based alloy matrix is used and TWIP steel powder is added as a toughening cutting additive. The working surface plating of the valve seat is processed through magnetron sputtering technology to form a Ni transition layer and Cr/Ni functional plating layer, and sintering and heat treatment are carried out in combination with temperature and pressure and mold wall lubrication technology.
It significantly improves the hardness, tensile strength, impact toughness and wear resistance of the valve seat, extends the service life, and reduces the difficulty of processing. It is suitable for high-performance engines in high-temperature environments.
Smart Images

Figure CN119736559A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of powder metallurgy manufacturing of key parts of automobile engines, and particularly relates to a high-temperature wear-resistant, corrosion-resistant, easy-to-cut engine valve seat ring and a powder metallurgy preparation process and application thereof. Background Art
[0002] With the rapid development of modern industrial technology, especially in the fields of high-end equipment manufacturing, aerospace, automobile manufacturing, etc., the requirements for material performance are becoming increasingly stringent. Among them, wear resistance, as one of the important indicators of material performance, directly affects the service life, safety and maintenance cost of equipment.
[0003] With the continuous recovery of the global economy and the rapid development of the manufacturing industry, the market demand for high wear-resistant composite materials continues to grow. In particular, in some harsh working environments, such as high temperature, high pressure, high-speed friction, etc., traditional materials are difficult to meet the demand. Therefore, the development of new high wear-resistant composite materials can not only effectively improve the performance and reliability of equipment, but also reduce the maintenance costs of enterprises and improve economic benefits.
[0004] As a new type of material, Fe-based composite materials have excellent wear resistance, corrosion resistance, high temperature performance and other characteristics. Compared with other materials, Fe-based composite materials have extremely high hardness and wear resistance, can withstand greater friction and impact, and effectively extend the service life of equipment. It also has good corrosion resistance and can operate stably for a long time in harsh environments such as acid and alkali. And it can still maintain good performance at high temperatures, which is suitable for work in high temperature environments.
[0005] The valve seat and valve are one of the important friction pairs of the engine. The function of the valve seat is to control the entry of fuel gas and the discharge of exhaust gas. The valve seat and valve cooperate to seal the combustion chamber to reduce the wear of the valve, and withstand the impact and wear of the valve in the high temperature environment; as well as the erosion and oxidation of the intake and exhaust flow. That is, when serving at high temperatures, it not only has to withstand high temperature and high stress impact, but also has to be corroded by exhaust gas, which is very easy to cause wear, deformation, burning, and even fracture failure. The valve seat is one of the vulnerable parts of the engine. When it is severely worn, it will cause the valve to sink too much and the airtightness is poor, which will cause failure and damage. The quality, performance and reliability of the valve seat directly affect the fuel consumption, power, efficiency and service life of the engine.
[0006] The main performance requirements of existing valve seat rings are high strength, wear resistance, corrosion resistance, high temperature resistance, etc., in order to ensure the normal operation of gasoline engines, diesel engines, natural gas engines and alcohol fuel engines. However, the high-end high temperature resistant, corrosion resistant and wear resistant material technology has long been monopolized by Japan, the United States, Germany and other countries. How to break through the foreign technology blockade is a restrictive problem currently faced by the automotive industry. Therefore, researching and developing new composite materials with high wear resistance, and developing high-end high temperature wear resistant, corrosion resistant and easy-to-cut engine valve seat rings are of great significance to promoting technological progress and industrial upgrading in related industries. Summary of the invention
[0007] In view of the harsh working environment requirements faced by valve seat rings in current high-performance engines and special fuel engines such as hydrogen fuel engines, as well as the shortcomings in the performance of valve seat rings in existing high-performance engines and special fuel engines such as hydrogen fuel engines, the present invention aims to invent an engine valve seat ring that is resistant to high temperature wear, corrosion, and easy to cut, and a preparation process thereof, which is suitable for engines of high-performance automobiles, hydrogen fuel automobiles, military heavy equipment, and large ships, etc.
[0008] The main technical content of the present invention is to design the alloy powder material composition used for the valve seat ring, add a special toughening and cutting additive, and at the same time obtain a valve seat ring preparation technology suitable for it, so as to solve the problems of high temperature, wear and corrosion of valves and valve seat rings caused by high speed, high temperature and repeated impact in the engine, as well as the problem of difficult cutting of high-hardness materials, reduce the processing difficulty of the valve seat ring, and extend the service life of the valve seat ring.
[0009] An object of the present invention is to provide an engine valve seat insert, which is made of an Fe-based alloy substrate by using a magnetron sputtering process to coat a working surface thereof, wherein the chemical composition of the Fe-based alloy substrate is as follows: C: 0.2-0.7%, Ti: 0.8%-1.2%, Mn: 0.5%-1.2%, Al: 0.5%-1.5%, Cr: 4.8%-8.0%, Co: 1.6%-2.4%, V: 2.0%-4.8%, Ni: 0.5%-1.0%, Mo: 5.0%-6.0%, Nb: 0.5%-1.0%, W: 3.0%-4.8%, B: 0.4%-0.8%, toughening and cutting additives 2.5-4.0%, hard particles 1.0-1.2%, solid lubricant 1.0-1.6%, balance Fe, particle size is 80-150 mesh.
[0010] Preferably, the toughening and cutting additive is twinning induced plasticity (TWIP) steel, and its chemical composition is: C: 0.4-0.8%, Mn: 20.0%-25.0%, Al: 1.0%-4.5%, Si: 1.0%-3.0%, Ni: 0.4%-1.0%, Cr: 0.2%-0.6%, and the balance is Fe.
[0011] In order to resolve the technical contradiction between high hardness and processing performance, an appropriate amount of TWIP steel powder is added to the matrix material. Its extremely high plasticity and low hardness are used to improve the cutting performance of the matrix material. At the same time, its outstanding work hardening characteristics are used to increase its own hardness when the valve seat ring is subjected to impact to offset the effect of its addition on the overall hardness of the material, thereby obtaining the wear resistance and cutting performance of the composite material.
[0012] Preferably, the hard particles are one or both of WC and NTi.
[0013] Preferably, the solid lubricant is graphite, Cu, MnS, MoS 2 Two or three of them.
[0014] Preferably, the working surface coating comprises: a Ni transition layer with a thickness of 0.2-0.5 μm; and a Cr / Ni functional coating with a thickness of 1.0-2.0 μm, which are prepared using magnetron sputtering technology.
[0015] Another object of the present invention is to provide a process for preparing an engine valve seat ring, wherein the specific preparation steps are as follows: (1) Preparation of toughening and cutting additives: Prepare raw materials according to the alloy composition ratio, use electric arc furnace smelting to prepare twinning induced plasticity (TWIP) steel, and use aerosol method to prepare TWIP steel powder, and screen and select TWIP steel powder with a powder size of 80-150 mesh as a toughening and cutting additive; (2) Mixing powder: Mix different metal powders in proportion by mass to form alloy powder with a powder particle size of 80-150 mesh, add toughening and cutting additives, hard particles and solid lubricants, and dry mix on a mixer for 30-80 minutes; (3) Mold wall lubrication: Add 0.25% of mold wall lubricant to lubricate the mold wall in the negative mold cavity of the valve seat ring. The lubricant is Zn[CH 3 (CH 2 ) 16 CO0] 2 ; (4) Warm pressing: Using a negative template with double floating and double-layer filler, the powder is warm pressed at 150-200°C and a pressure of 750-1000MPa to obtain a valve seat ring green body; (5) Sintering: The formed valve seat ring green body is placed in a push rod furnace and sintered at N 2 Three-stage sintering is adopted under protective atmosphere, firstly pre-sintering is carried out at 600-750℃ for 1.0-2.0h, then secondary sintering is carried out at 900-1000℃ for 1.0-2.0h, and finally final sintering is carried out at 1100℃-1200℃ for 2.0-3.0h. After sintering, it is cooled naturally to obtain the desired sintered product; (6) Heat treatment: Heat treatment is carried out in a box furnace. The heat treatment process is to keep the temperature at 880-900℃ for 1.0-2.0h and then quench. Then, keep the temperature at the tempering temperature of 250-300℃ for 1.0-2.0h and then cool in the furnace. (7) Finishing: Use CNC machine tools to finish the valve seat ring; (8) Transition layer: The Ni transition layer was prepared by magnetron sputtering technology. Ar was used as the protective gas for magnetron sputtering. The target material was Ni. The distance between the target material and the valve seat insert substrate was 80-100 mm. The deposition pressure was 0.2-1.0 Pa. The target bias voltage was 500-800 V. The target current density was 5-10 mA / cm 2 , power density is 10-30W / cm 2 , the deposition rate is 200-400nm / min, the working temperature is 200-250℃, and the thickness of the Ni transition layer is 0.2-0.5μm; (9) Cr / Ni functional coating: The Cr / Ni functional coating was prepared by magnetron sputtering technology. Ar was used as the protective gas for magnetron sputtering. The target material was Cr / Ni. The distance between the target material and the valve seat insert substrate was 80-100 mm. The deposition pressure was 0.2-1.0 Pa. The target bias voltage was 500-800 V. The target current density was 5-10 mA / cm 2 , power density is 10-30W / cm 2 , the deposition rate is 300-600nm / min, the working temperature is 250-280℃, and the thickness of the Cr / Ni functional coating is 1.0-2.0μm.
[0016] Preferably, the lubricant is Zn[CH 3 (CH 2 ) 16 CO0] 2 .
[0017] Preferably, the density of the valve seat ring prepared by this process is 7.8-8.1 g / cm 3 , tensile strength is 750-800MPa, impact toughness is 12-15J / cm 2, hardness ≥ HRC53, crushing strength after heat treatment ≥ 1250MPa, valve sinking after 1000h of wear-resistant bench test at 1000℃ is 80-100μm, interference <80μm, engine bench 8×10 5 After two reciprocating strokes, the wear loss is ≤15μm, the oxidation weight gain rate is ≤0.06%; the vulcanization weight gain rate is ≤0.60%.
[0018] Another object of the present invention is to provide the application of the above-mentioned engine valve seat ring in the preparation of accessories for engines including but not limited to hydrogen, natural gas, LPG gas, oil-gas hybrid power, and fuel oil.
[0019] Compared with the existing powder metallurgy valve seat ring for engines, the beneficial effects of the present invention are as follows: 1. The Fe-based alloy matrix in the valve seat ring of the present invention contains elements such as C, Ti, Mn, Al, Cr, Co, V, Ni, Mo, Nb, W, and B, which have a good effect on the strength, hardness, toughness, wear resistance, high temperature performance and corrosion resistance of the Fe-based alloy, and can make the valve seat ring have higher hardness, toughness, wear resistance, and good high temperature performance and corrosion resistance.
[0020] Since solid solution strengthening and martensite / carbide / precipitation phase strengthening are the most common toughening and hardening mechanisms of Fe-based alloys, in order to ensure that Fe-based alloys still have high toughness and hardness at high temperatures, special alloying elements and their contents must be selected to form stable martensite and carbide hard phases at high temperatures. The present invention obtains an alloy matrix with solid solution / martensitic phase transformation / dispersion strengthening characteristics through multi-component alloying such as C, Cr, Ni, Mo and W and microalloying and post-processing processes such as V, Ti and B. Wherein higher C, Cr, Ni and Mo content will increase the alloy element solid solution amount of the martensitic phase. Combined with the addition of W, complex carbides containing Cr and W can be formed, thereby simultaneously improving the hardness and high temperature stability of the martensitic matrix and carbides. In addition, the addition of elements such as V, Ti and B is intended to form a high-hardness dispersed precipitation phase to further improve the overall hardness of the matrix.
[0021] Co can improve high temperature strength, thermal fatigue resistance, high temperature sulfur corrosion resistance and oxidation resistance, increase the nucleation rate of carbides, reduce their growth rate, make carbides precipitate in a fine dispersed state, and can stably exist at high temperatures, playing a strengthening role. In addition, Co can also improve the high temperature sulfur corrosion resistance of valve seat rings, improve the morphology and distribution of second phases such as Cr, W, and Mo, and improve wear resistance.
[0022] Carbon / nitrogen compounds are industrial ceramic materials with high stability and hardness. Typical carbides such as Cr 7 C 3, WC, etc., and typical nitrides include NTi, SiN, etc. Therefore, the present invention obtains in-situ self-generated (Cr, Fe) by designing the Cr / C ratio of the matrix. 7 C 3 type carbide; hard particles are introduced by adding WC and NTi; the wettability of hard particles and Fe matrix is improved by surface treatment; and good metallurgical bonding is formed between hard phase particles and matrix through high temperature sintering.
[0023] 2. The present invention uses TWIP steel powder as a toughening and cutting additive, which well balances the technical contradiction between the wear resistance and cutting processability of high-hardness materials.
[0024] After the valve seat ring is pressed into powder, sintered and heat treated, it must be cut and then press-fitted with the cylinder block. However, due to the high hardness and high wear resistance of the material, the cutting performance of the product is often poor, and the alarm is often triggered due to excessive pressure during press-fitting, resulting in the product being scrapped.
[0025] Twinning Induced Plasticity (TWIP) steel is a new type of high alloy steel with outstanding plasticity and toughness. Its tensile strength is usually above 1000MPa, and its elongation after fracture can still be as high as 60%. Another feature of TWIP steel is the significant work hardening effect, and the yield strength ratio is generally less than 0.35. After a certain work hardening treatment, the hardness of TWIP steel can reach HRC45 or above.
[0026] 3. The present invention adopts warm pressing + die wall lubrication technology, and the density of the sintered powder metallurgy valve seat ring reaches 7.8-8.1g / cm 3 , ensuring that the valve seat ring has high strength, hardness and wear resistance.
[0027] 4. The high temperature wear resistant, corrosion resistant and easy-to-cut engine valve seat provided by the present invention has a tensile strength of 750-800MPa and an impact toughness of 12-15J / cm 2 , hardness ≥HRC53.
[0028] 5. The crushing strength of the engine valve seat ring of the present invention after heat treatment is ≥1250MPa, the valve sinking amount is 80-100μm after 1000 hours of wear-resistant bench test at 1000℃, and the interference is <80μm. Engine bench 8×10 5 Wear loss after reciprocating times ≤15μm. Oxidation weight gain ≤0.06%; vulcanization weight gain ≤0.60%.
[0029] 6. The magnetron sputtering technology adopted in the present invention to prepare the transition Ni layer and the functional Cr / Ni coating can further improve the hardness, strength, wear resistance and corrosion resistance of the working surface of the valve seat insert.
[0030] The high temperature wear resistant, corrosion resistant and easy-to-cut engine valve seat ring prepared by the present invention has excellent density, high corrosion resistance, high wear resistance and good high temperature performance, and is easy to cut. It can be used for the preparation of accessories including but not limited to hydrogen, natural gas (CNG, LNG), LPG gas, oil and gas hybrid power, and fuel engine to meet the working conditions under high temperature, dry friction, impact, gas corrosion and other environmental conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 The figure is a metallographic structure diagram of the sintered state of the engine valve seat ring prepared by the present invention.
[0032] Figure 2 The metallographic structure diagram of the engine valve seat ring prepared by the present invention after heat treatment.
[0033] Figure 1 The microstructure is mainly composed of pearlite, a small amount of martensite and carbide; Figure 2 The microstructure after heat treatment is tempered troostite, pearlite and dispersed carbide particles. This composite strengthening structure not only meets the strength, hardness and density requirements of the valve seat ring, but also has certain plasticity, impact toughness, high temperature wear resistance and corrosion resistance, and has excellent comprehensive performance. DETAILED DESCRIPTION
[0034] In order to better understand the technical content, technical route, technical features, application scenarios, etc. of the engine valve seat ring of the patented invention, the following implementation examples include but are not limited to the present invention.
[0035] Example 1 The Fe-based alloy substrate is processed by using a magnetron sputtering process to coat the working surface.
[0036] The chemical composition (mass fraction) of the Fe-based alloy matrix is as follows: C: 0.4%, Ti: 0.8%, Mn: 1.1%, Al: 1.0%, Cr: 5.5%, Co: 1.6%, V: 2.5%, Ni: 0.6%, Mo: 6.0%, Nb: 0.5%, W: 3.2%, B: 0.4%, 2.5% toughening and cutting additives, 1.0% hard particles, 1.0% solid lubricant, and the remainder Fe. The particle size is 130 mesh.
[0037] The toughening and cutting additive is TWIP steel, and its chemical composition is: C: 0.8%, Mn: 21.5%, Al: 2.0%, Si: 1.8%, Ni: 0.8%, Cr: 0.2%, and the balance is Fe.
[0038] The hard particles are WC and NTi, accounting for 50%:50% respectively. The solid lubricants are graphite and Cu, accounting for 50%:50% respectively.
[0039] The high temperature resistant and wear resistant coating on the working surface includes: a Ni transition layer with a thickness of 0.25 μm; and a Cr / Ni functional coating with a thickness of 1.6 μm.
[0040] (1) preparing raw materials according to the alloy composition ratio, using electric arc furnace smelting to prepare TWIP steel, and using aerosol method to prepare TWIP steel powder, and screening to select TWIP steel powder with a powder size of 130 mesh as a toughening and cutting additive; (2) Mix different metal powders in a certain proportion to form alloy powder with a powder particle size of 130 mesh. Add toughening and cutting additives, hard particles and solid lubricants, and dry mix in a mixer for 80 minutes; (3) Add 0.25% by mass of die wall lubricant Zn[CH 3 (CH 2 ) 16 CO0] 2 , lubricate the mold wall in the female mold cavity of the valve seat ring; (4) Using a negative template with double floating and double-layer filler, the powder is warm-pressed at 160°C and 800MPa; (5) Place the formed valve seat ring green body into a push rod furnace and heat it at N 2 To protect the atmosphere, pre-sintering was performed at 700°C for 2.0 h, then secondary sintering was performed at 1000°C for 1 h, and finally final sintering was performed at 1200°C for 3.0 h. After sintering, it was cooled naturally; (6) Heat treatment is performed in a box furnace, at a temperature of 900°C for 1.0 h, followed by quenching, and then at a tempering temperature of 300°C for 2.0 h and furnace cooling; (7) Use CNC machine tools to finish the valve seat ring; (8) Magnetron sputtering technology was used to prepare the transition layer and functional coating. Ar was used as the protective gas, the target material was Ni, the distance between the target material and the valve seat insert substrate was 100 mm, the deposition pressure was 1.0 Pa, the target bias voltage was 600 V, and the target current density was 8 mA / cm 2 , power density is 20W / cm 2 , the deposition rate is 400nm / min, the working temperature is 250℃, and the Ni transition layer thickness is 0.25μm; (9) Ar was used as the protective gas, the target material was Cr / Ni, the distance between the target material and the valve seat insert substrate was 100 mm, the deposition pressure was 0.8 Pa, the target bias voltage was 600 V, and the target current density was 8 mA / cm 2 , power density is 20W / cm 2, the deposition rate is 400nm / min, the working temperature is 250℃, and the thickness of the Cr / Ni functional coating is 1.6μm.
[0041] After testing, its density is 8.0g / cm, tensile strength is 760MPa, and impact toughness is 13.9J / cm 2 , hardness is 54HRC, crushing strength is 1310MPa, at 1000℃, after 1000 hours of engine bench test, its sinking amount is 80μm, interference is 70μm, engine bench 8×10 5 After two reciprocating strokes, the wear loss is 10μm, the oxidation weight gain rate is 0.05%; the vulcanization weight gain rate is ≤0.5%.
[0042] Example 2 The Fe-based alloy substrate is processed by using a magnetron sputtering process to coat the working surface.
[0043] The chemical composition (mass fraction) of the Fe-based alloy matrix is as follows: C: 0.5%, Ti: 1.0%, Mn: 1.0%, Al: 1.2%, Cr: 6.0%, Co: 2.0%, V: 3.5%, Ni: 0.5%, Mo: 5.0%, Nb: 0.8%, W: 4.0%, B: 0.5%, 3.0% toughening and cutting additives, 1.0% hard particles, 1.5% solid lubricant, and the remainder Fe. The particle size is 90 mesh.
[0044] The toughening and cutting additive is TWIP steel, and its chemical composition is: C: 0.6%, Mn: 23.5%, Al: 2.0%, Si: 1.5%, Ni: 0.4%, Cr: 0.4%, and the balance is Fe.
[0045] The hard particles are WC. The solid lubricants are graphite and MoS 2 , accounting for 40%:60% respectively.
[0046] The high temperature resistant and wear resistant coating on the working surface includes: a Ni transition layer with a thickness of 0.4 μm; a Cr / Ni functional coating with a thickness of 1.2 μm, which is prepared using magnetron sputtering technology.
[0047] The specific preparation steps of the above-mentioned engine valve seat ring are as follows: (1) Preparation of toughening and cutting additives: Prepare raw materials according to the alloy composition ratio, use electric arc furnace smelting to prepare TWIP steel, and use aerosol method to prepare TWIP steel powder, and screen and select TWIP steel powder with a powder size of 90 mesh as a toughening and cutting additive; (2) Mixing powder: Mix different metal powders in proportion to form alloy powder with a powder particle size of 90 mesh, add toughening and cutting additives, hard particles and solid lubricants, and dry mix on a mixer for 50 minutes; (3) Add mold wall lubrication: Add 0.25% mass fraction of mold wall lubricant Zn[CH 3 (CH 2 ) 16 CO0] 2 , lubricate the mold wall in the female mold cavity of the valve seat ring; (4) Warm pressing: The powder is warm pressed at 200°C and 1000 MPa using a double-floating negative template and double-layer filler. (5) Sintering: The formed valve seat ring green body is placed in a push rod furnace and sintered at N 2 To protect the atmosphere, pre-sintering was performed at 750°C for 1.5 h, then secondary sintering was performed at 1000°C for 2.0 h, and finally final sintering was performed at 1200°C for 3.0 h. After sintering, the steel was cooled naturally; (6) Heat treatment: Heat treatment is carried out in a box furnace, at a temperature of 900°C for 2.0 h, then quenching, and then at a tempering temperature of 300°C for 2.0 h, then furnace cooling; (7) Finishing: Use CNC machine tools to finish the valve seat ring; (8) Magnetron sputtering transition layer: The transition layer and functional coating are prepared using magnetron sputtering technology. Ar is used as the protective gas, the target material is Ni, the distance between the target material and the valve seat insert substrate is 100 mm, the deposition pressure is 0.5 Pa, the target bias voltage is 600 V, and the target current density is 8 mA / cm 2 , power density is 20W / cm 2 , the deposition rate is 300nm / min, the working temperature is 240℃, and the thickness of the Ni transition layer is 0.5μm; (9) Magnetron sputtering functional coating: Ar is used as the protective gas, the target material is Cr / Ni, the distance between the target material and the valve seat insert substrate is 100 mm, the deposition pressure is 0.9 Pa, the target bias voltage is 800 V, and the target current density is 9 mA / cm 2 , power density is 16W / cm 2 , the deposition rate is 600nm / min, the working temperature is 250℃, and the thickness of the Cr / Ni functional coating is 1.5μm.
[0048] After testing, its density is 8.0g / cm, tensile strength is 780MPa, and impact toughness is 12.7J / cm 2, hardness is 55HRC, crushing strength is 1300MPa, at 1000℃, after 1000 hours of engine bench test, its sinking amount is 90μm, interference is 70μm, engine bench 8×10 5 After two reciprocating strokes, the wear loss is 10μm, the oxidation weight gain rate is 0.05%; the vulcanization weight gain rate is ≤0.5%.
[0049] Example 3 The Fe-based alloy substrate is processed by using a magnetron sputtering process to coat the working surface.
[0050] The chemical composition (mass fraction) of the Fe-based alloy matrix is as follows: C: 0.6%, Ti: 1.2%, Mn: 0.8%, Al: 1.0%, Cr: 7.2%, Co: 1.8%, V: 4.0%, Ni: 0.8%, Mo: 5.0%, Nb: 1.0%, W: 4.2%, B: 0.6%, 4.0% toughening and cutting additives, 1.2% hard particles, 1.6% solid lubricant, and the remainder Fe. The particle size is 120 mesh.
[0051] The toughening and cutting additive is TWIP steel, and its chemical composition is: C: 0.5%, Mn: 22.0%, Al: 1.5%, Si: 1.2%, Ni: 0.6%, Cr: 0.5%, and the balance is Fe.
[0052] The hard particles are NTi. The solid lubricants are MnS and MoS 2 , accounting for 50%:50% respectively.
[0053] The high temperature resistant and wear resistant coating on the working surface includes: a Ni transition layer with a thickness of 0.3 μm; and a Cr / Ni functional coating with a thickness of 1.0 μm.
[0054] The specific preparation steps of the above-mentioned engine valve seat ring are as follows: (1) Preparation of toughening and cutting additives: Prepare raw materials according to the alloy composition ratio, use electric arc furnace smelting to prepare TWIP steel, and use aerosol method to prepare TWIP steel powder, and screen and select TWIP steel powder with a powder size of 120 mesh as a toughening and cutting additive; (2) Mixing powder: Mix different metal powders in a certain proportion to form alloy powder with a powder particle size of 120 mesh, add toughening and cutting additives, hard particles and solid lubricants, and dry mix on a mixer for 60 minutes; (3) Die wall lubrication: Add 0.25% by mass of die wall lubricant Zn[CH 3 (CH 2 ) 16 CO0] 2, lubricate the mold wall in the female mold cavity of the valve seat ring; (4) Warm pressing: The powder is warm pressed at 180°C and 800MPa using a double-floating negative template and double-layer filler. (5) Sintering: The formed valve seat ring green body is placed in a push rod furnace and sintered at N 2 To protect the atmosphere, pre-sintering was performed at 700°C for 1.2h, then secondary sintering was performed at 950°C for 1.5h, and finally final sintering was performed at 1150°C for 2.0h. After sintering, it was cooled naturally; (6) Heat treatment: Heat treatment is carried out in a box furnace, at a temperature of 880°C for 2.0 h, then quenching, and then at a tempering temperature of 280°C for 2.0 h, followed by furnace cooling; (7) Finishing: Use CNC machine tools to finish the valve seat ring; (8) Magnetron sputtering transition layer: The transition layer and functional coating are prepared using magnetron sputtering technology. Ar is used as the protective gas, the target material is Ni, the distance between the target material and the valve seat insert substrate is 80 mm, the deposition pressure is 1.0 Pa, the target bias voltage is 800 V, and the target current density is 10 mA / cm 2 , power density is 10W / cm 2 , the deposition rate is 200nm / min, the working temperature is 200℃, and the Ni transition layer thickness is 0.3μm; (9) Magnetron sputtering functional coating: Ar is used as the protective gas, the target material is Cr / Ni, the distance between the target material and the valve seat insert substrate is 80 mm, the deposition pressure is 0.2 Pa, the target bias voltage is 800 V, and the target current density is 6 mA / cm 2 , power density is 10W / cm 2 , the deposition rate is 300nm / min, the working temperature is 280℃, and the thickness of the Cr / Ni functional coating is 1.0μm.
[0055] After testing, its density is 7.8g / cm, tensile strength is 760MPa, and impact toughness is 14.5J / cm 2 , hardness is 58HRC, crushing strength is 1320MPa, at 1000℃, after 1000 hours of engine bench test, its sinking amount is 95μm, interference is 80μm, engine bench 8×10 5 The wear loss after reciprocating is 20μm, the oxidation weight gain rate is 0.05%; the vulcanization weight gain rate is ≤0.5%.
[0056] Comparative Example 1 Compared with Example 1 of the present invention, the difference between this ratio and Example 1 is that the content of the toughening and cutting additive in this comparative example 1 is 0.
[0057] After testing, its density is 8.0g / cm, tensile strength is 760MPa, and impact toughness is 13.9J / cm 2 , hardness is 54HRC, crushing strength is 1310MPa, at 1000℃, after 1000 hours of engine bench test, its sinking amount is 80μm, interference is 70μm, engine bench 8×10 5 After two reciprocating strokes, the wear loss is 10μm, the oxidation weight gain rate is 0.05%; the vulcanization weight gain rate is ≤0.5%.
[0058] It can be seen from Examples 1-3 and Comparative Example 1 that as the content of the toughening and cutting additive increases, the tensile strength of the valve seat ring gradually increases, but its impact toughness first decreases and then increases, indicating that when the content of the toughening and cutting additive reaches 3.0%, the valve seat ring material has the best easy-to-cut performance; at the same time, the sinking amount of the valve seat ring first increases and then decreases, and the wear amount first remains unchanged and then increases, indicating that the wear resistance of the valve seat ring is stable.
[0059] In addition, it can be seen from Examples 1-3 that, as the content of the toughening and cutting additive increases, the hardness and tensile strength of the valve seat ring are continuously enhanced by increasing the content of Ti, Cr, Co, V, W, and B.
Claims
1. An engine valve seat ring, characterized in that: It is made of Fe-based alloy substrate by magnetron sputtering process and coating on its working surface, wherein the chemical composition of Fe-based alloy substrate is as follows: C: 0.2-0.7%, Ti: 0.8%-1.2%, Mn: 0.5%-1.2%, Al: 0.5%-1.5%, Cr: 4.8%-8.0%, Co: 1.6%-2.4%, V: 2.0%-4.8%, Ni: 0.5%-1.0%, Mo: 5.0%-6.0%, Nb: 0.5%-1.0%, W: 3.0%-4.8%, B: 0.4%-0.8%, toughening and cutting additives 2.5-4.0%, hard particles 1.0-1.2%, solid lubricant 1.0-1.6%, balance Fe, particle size is 80-150 mesh.
2. The engine valve seat ring according to claim 1, characterized in that: The toughening and cutting additive is twinning induced plasticity steel, and its chemical composition is: C: 0.4-0.8%, Mn: 20.0%-25.0%, Al: 1.0%-4.5%, Si: 1.0%-3.0%, Ni: 0.4%-1.0%, Cr: 0.2%-0.6%, and the balance is Fe.
3. The engine valve seat ring according to claim 1, characterized in that: The hard particles are one or two of WC and NTi.
4. The engine valve seat ring according to claim 1, characterized in that: The solid lubricant is two or three of graphite, Cu, MnS and MoS2.
5. The engine valve seat ring according to claim 1, characterized in that: The working surface coating comprises: a Ni transition layer with a thickness of 0.2-0.5 μm; a Cr / Ni functional coating with a thickness of 1.0-2.0 μm, which is prepared by using magnetron sputtering technology.
6. The process for preparing an engine valve seat ring according to any one of claims 1 to 5, characterized in that: The specific preparation steps are as follows: (1) Preparation of toughening and cutting additives: Prepare raw materials according to the alloy composition ratio, use electric arc furnace smelting to prepare TWIP steel, and use aerosol method to prepare TWIP steel powder, and screen and select TWIP steel powder with a powder size of 80-150 mesh as a toughening and cutting additive; (2) Mixing powder: Mix different metal powders in proportion to form alloy powder with a powder particle size of 80-150 mesh, add toughening and cutting additives, hard particles and solid lubricants, and dry mix on a mixer for 30-80 minutes; (3) Mold wall lubrication: Add 0.25% of mold wall lubricant by mass to lubricate the mold wall in the female mold cavity of the valve seat ring; (4) Warm pressing: The powder is warm pressed at 150-200°C and 750-1000MPa using a double-floating negative template and double-layer filler; (5) Sintering: The formed valve seat ring green body is placed in a push rod furnace, and the valve seat is prepared by a three-stage sintering method under N2 as a protective atmosphere. First, pre-sintering is carried out at 600-750℃ for 1.0-2.0h, then secondary sintering is carried out at 900-1000℃ for 1.0-2.0h, and finally final sintering is carried out at 1100℃-1200℃ for 2.0-3.0h. After sintering, it is naturally cooled to obtain the desired sintered product; (6) Heat treatment: Heat treatment is carried out in a box furnace. The heat treatment process is to keep the temperature at 880-900℃ for 1.0-2.0h and then quench. Then, keep the temperature at the tempering temperature of 250-300℃ for 1.0-2.0h and then cool in the furnace. (7) Finishing: Use CNC machine tools to finish the valve seat ring; (8) Transition layer: The Ni transition layer is prepared by magnetron sputtering technology, and the thickness of the Ni transition layer is 0.2-0.5 μm; (9) Cr / Ni functional coating: The Cr / Ni functional coating is prepared by magnetron sputtering technology, and the thickness of the Cr / Ni functional coating is 1.0-2.0 μm.
7. The process for preparing an engine valve seat ring according to claim 6, characterized in that: The lubricant is Zn[CH3(CH2) 16 CO0]2.
8. The process for preparing an engine valve seat ring according to claim 6, characterized in that: The density of the valve seat ring prepared by this process is 7.8-8.1g / cm 3 , tensile strength is 750-800MPa, impact toughness is 12-15J / cm 2 , hardness ≥ HRC53, crushing strength after heat treatment ≥ 1250MPa, valve sinking after 1000h of wear-resistant bench test at 1000℃ is 80-100μm, interference <80μm, engine bench 8×10 5 After two reciprocating strokes, the wear loss is ≤15μm, the oxidation weight gain rate is ≤0.06%; the vulcanization weight gain rate is ≤0.60%.
9. The engine valve seat ring as described in any one of claims 1 to 5 is used in the preparation of engine accessories including but not limited to hydrogen, natural gas, LPG gas, oil and gas hybrid power, and fuel oil.
Citation Information
Cited By
High-performance powder metallurgy alloy, engine valve seat ring and preparation method of engine valve seat ring
CN121472727A